Formononetin Ameliorates Renal Dysfunction, Oxidative Stress, Inflammation, and Apoptosis and Upregulates Nrf2/HO-1 Signaling in a Rat Model of Gentamicin-Induced Nephrotoxicity - Althunibat, Osama Y.; Abukhalil, Mohammad H.; Aladaileh, Saleem H.; Qaralleh, Haitham; Al-Amarat, Wesam; Alfwuaires, Manal A.; Algefare, Abdulmohsen I.; Namazi, Nader Ibrahim; Melebary, Sahar J.; Babalghith, Ahmad O.; Conte-Junior, Carlos Adam (Frontiers in Pharmacology, 2022)
Gentamicin (GEN) is a bactericidal aminoglycoside applied to overcome gram-negative bacterial diseases; unfortunately, it is well-known to cause nephrotoxicity, which restricts its clinical use. Formononetin (FN) is a potent flavonoid that exhibits numerous promising pharmacological activities. In this study, we have assessed the nephroprotective efficacy of FN versus GEN-inducted renal injury in rats. Rats received FN (60 mg/kg/day (d), orally for 2 weeks) and GEN (100 mg/kg/day, i.p. from d 8 to d 14). GEN-treated rats demonstrated increased urea and creatinine levels in serum, associated with marked histopathological changes in the kidney. Malondialdehyde (MDA) and protein carbonyl contents were elevated, whereas the concentration of glutathione and the levels of catalase and superoxide dismutase were lowered in GEN-administered rats. FN largely prevented tissue damage, attenuated renal function, reduced MDA and protein carbonyl, and enhanced antioxidant capacity in the kidney of GEN- administrated animals. Kidney of GEN-treated rats demonstrated elevated Bax and caspase-3 protein expression (Expr.), accompanied by lowered Bcl-2 protein Expr., an effect that FN attenuated. Moreover, FN treatment caused upregulation of Nrf2 and HO-1 Expr. in renal tissue of GEN-injured animals. Collectively, FN protects versus GEN-caused renal damage via exhibiting antioxidant, anti-inflammatory, and antiapoptotic activities and augmenting Nrf2 signaling, suggesting FN as a promising agent for preventing drug-induced organ damage.